Gancidin W, a potential low toxicity antimalarial agent isolated from an Endophytic Streptomyces SUK10 - Baba, Mohd Shukri; Abu Hassan, Zainal Abidin; Latip, Jalifah; Herron, Paul R.; Pethick, Florence; Edrada-Ebel, RuAngelie; Mohamad Zin, Noraziah (2016)
As it resisted against nearly all current drugs, malaria was reported remained as the most threatening human parasitic disease. In line with this, endophytic Streptomyces are potential sources for novel bioactive molecules. In this study, prolyl-leucyl-diketopiperazine (C11H18N2O2) or Gancidin W (GW) was successfully isolated from Streptomyces SUK10 that inhabited in the bark of Shorea ovalis. Using four days suppressive test (4DST), this compound was in-vivo tested against Plasmodium berghei NK65. At 6.25 and 3.125 µg kg-1 body weight (bw), there was a very significant relationship of the ability to inhibit the growth of P. berghei NK65 when GW exhibited an inhibition rate of nearly 80% on male ICR strain mice. Comparing GW with dH2O diluted quinine hydrochloride and 0.9% normal saline as positive and negative controls respectively, 50% of the mice group treated with 3.125 µg kg-1 bw was managed to survive more than eight months post-infection exposure where this survival ranged was exceeded half of the normal mice’s life span period. As in-vivo toxicity assessment towards selected vital organs and blood enzymes were also investigated, the ALT and AST enzymes level was slightly higher but there was no abnormalities and injuries were found on the tested organs of the mice group treated with GW at this concentration. These findings indicated that GW isolated from Streptomyces SUK10 exhibited very low toxicity and is a good candidate as a potential antimalarial agent.